2018
DOI: 10.1016/s0140-6736(18)32261-x
|View full text |Cite
|
Sign up to set email alerts
|

Albiglutide and cardiovascular outcomes in patients with type 2 diabetes and cardiovascular disease (Harmony Outcomes): a double-blind, randomised placebo-controlled trial

Abstract: Background: Glucagon-like peptide 1 agonists differ in chemical structure, duration of action and in their effects on clinical outcomes. The cardiovascular effects of once-weekly albiglutide in type 2 diabetes are unknown. Methods: We randomly assigned patients with type 2 diabetes and cardiovascular disease to the addition of once-weekly subcutaneous injection of albiglutide (30 mg to 50 mg) or matching placebo to standard care. We hypothesized that albiglutide would be noninferior to placebo for the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
943
1
35

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,353 publications
(1,012 citation statements)
references
References 23 publications
10
943
1
35
Order By: Relevance
“…The emergence of new approaches to glucose lowering with proven cardiovascular and renal benefits (ie, sodium‐glucose co‐transporter‐2 [SGLT‐2] inhibitors and glucagon‐like peptide‐1 [GLP‐1] agonists) has created further uncertainty as to the value of aiming for near normal glycaemic targets without consideration of the agents used. Indeed, the growing body of trial evidence would suggest that the agents used, at least over the short term (2‐5 years), may be even more important (especially in high‐risk patients with clinically apparent cardiovascular or renal disease) . The EMPA‐Reg, CANVAS, DECLARE‐TIMI and CREDENCE trials all reported the superiority of the introduction of SGLT‐2 inhibitors compared with placebo and standard care among patients with type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of new approaches to glucose lowering with proven cardiovascular and renal benefits (ie, sodium‐glucose co‐transporter‐2 [SGLT‐2] inhibitors and glucagon‐like peptide‐1 [GLP‐1] agonists) has created further uncertainty as to the value of aiming for near normal glycaemic targets without consideration of the agents used. Indeed, the growing body of trial evidence would suggest that the agents used, at least over the short term (2‐5 years), may be even more important (especially in high‐risk patients with clinically apparent cardiovascular or renal disease) . The EMPA‐Reg, CANVAS, DECLARE‐TIMI and CREDENCE trials all reported the superiority of the introduction of SGLT‐2 inhibitors compared with placebo and standard care among patients with type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…All the test drugs showed their noninferiority to placebo with regard to their primary endpoint. In five of the twelve CVOTs, the Albiglutide and Cardiovascular Outcomes in Patients with Type 2 Diabetes and Cardiovascular Disease (HARMONY), the Liraglutide Effect and Action in Diabetes: Evaluation of Cardiovascular Outcome Results (LEADER), the Semaglutide and Cardiovascular Outcomes in Patients with Type 2 Diabetes (SUSTAIN‐6), the Canagliflozin Cardiovascular Assessment Study (CANVAS), and the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA‐REG OUTCOME), the primary CV endpoint was significantly lower in the test drug than the placebo group. The CV efficacy shown in the five CVOTs was achieved alongside moderate glycemic control, with HbA1c values not less than 6.8% (Table ), as recommended by the ACP guidance …”
Section: Hba1c Targets and CV Risk Reduction Associated With Newer Glmentioning
confidence: 99%
“…nary syndrome, the rate of HAHF was 4.0% with lixisenatide and 4.2% with placebo (HR 0.96, 95% CI 0.75-1.23; P = 0.75) 160. HAHF combined with cardiac death was 4% in the albiglutide group and 5% in the placebo group (HR 0.85, 95% CI 0.7-1.04; P = 0.113) 161. HAHF combined with cardiac death was 4% in the albiglutide group and 5% in the placebo group (HR 0.85, 95% CI 0.7-1.04; P = 0.113) 161.…”
mentioning
confidence: 98%